Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1038/sj.ejhg.5200206
|View full text |Cite
|
Sign up to set email alerts
|

Migraine, ataxia and epilepsy: a challenging spectrum of genetically determined calcium channelopathies

Abstract: Clinical and genetic heterogeneity as well as influence of environmental factors have hampered identification of the genetic factors which are involved in episodic diseases such as migraine, episodic ataxia and epilepsy. The study of rare, but clearly genetically determined subtypes, may help to unravel the pathogenesis of the more common forms. Recently, different types of mutation in the brain-specific P/Q type calcium channel α 1A subunit gene (CACNA1A) on chromosome 19p13 were shown to be involved in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 79 publications
1
50
0
Order By: Relevance
“…CACNA1A codes for a voltagedependent, P/Q-type, alpha-1A subunit calcium channel and ATP1A2 for a Na + , K + -ATPase alpha-2 subunit. These findings lead to the hypothesis that migraine could be a channelopathy, something that resides in the neuronal membrane, making it more excitable [3,4]. Similar breakthroughs are awaited for the more common migraine forms, migraine with and without aura.…”
Section: Introductionmentioning
confidence: 99%
“…CACNA1A codes for a voltagedependent, P/Q-type, alpha-1A subunit calcium channel and ATP1A2 for a Na + , K + -ATPase alpha-2 subunit. These findings lead to the hypothesis that migraine could be a channelopathy, something that resides in the neuronal membrane, making it more excitable [3,4]. Similar breakthroughs are awaited for the more common migraine forms, migraine with and without aura.…”
Section: Introductionmentioning
confidence: 99%
“…myasthenia gravis, Lambert Eaton myasthenic syndrome and acquired neuromyotonia (Isaac's disease) . Often termed autoimmune channelopathies, these contrast with genetic channelopathies in which a loss or decrease in function is conferred by gene mutation with similar phenotypic consequences (Terwindt et al 1998). …”
Section: 'Classical' Antibody-mediated Neurological Diseasesmentioning
confidence: 99%
“…They found that sibling pairs with MA inherited the same 19p13 CACNA1A containing region significantly more frequently than expected by chance, consistently with an important involvement of this region in migraine, especially MA. Such results had led previously to the contention that the typical migraines could be conceptualized as calcium channelopathies, a concept useful also in explaining their co-morbidity with ataxia and epilepsy, and applicable also to the animal models displaying mutations in the murine homologue of the human CACNA1A gene [13].…”
Section: Migraine As a Channelopathymentioning
confidence: 99%